Developing an Artificial Neural Network for Modeling and Prediction of Temporal Structure and Spectral Composition of Environmental Noise in Cities - Torija, Antonio J.; Ruiz, Diego P.; Ramos-Ridao, Ángel (IntechOpen, 2011)
None